2018
DOI: 10.1371/journal.pgen.1007263
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminal of CASY-1/Calsyntenin regulates GABAergic synaptic transmission at the Caenorhabditis elegans neuromuscular junction

Abstract: The C. elegans ortholog of mammalian calsyntenins, CASY-1, is an evolutionarily conserved type-I transmembrane protein that is highly enriched in the nervous system. Mammalian calsyntenins are strongly expressed at inhibitory synapses, but their role in synapse development and function is still elusive. Here, we report a crucial role for CASY-1 in regulating GABAergic synaptic transmission at the C. elegans neuromuscular junction (NMJ). The shorter isoforms of CASY-1; CASY-1B and CASY-1C, express and function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 95 publications
(99 reference statements)
0
21
0
Order By: Relevance
“…82 Similar GABAergic neuron-specific effects to those we observed were seen with inhibition of the anaphase promoting complex and EEL-1 ubiquitin ligases, the F-box protein MEC-15 FBXW9, as well as the cell adhesion molecule CASY-1, in prior studies at this synapse. 48,80,81,83 These collective results demonstrate GABAergic neuron-specific regulation is possible, and even common, and that the aldicarb paralysis assay may be particularly sensitive to defects in inhibitory neurons. 50 We found that GABAergic neuron-specific overexpression not only of wild type UBC-9 but also the C93S mutant increased muscle excitation (Figure 6a), suggesting UBC-9's effects may be independent of its catalytic activity; however, because of the overexpression context, we believe this does not necessarily reflect a SUMOylation-independent role for endogenous UBC-9 at this synapse.…”
Section: Tight Regulation Of Ubc-9 Activity Is Required In Gabaergic mentioning
confidence: 72%
“…82 Similar GABAergic neuron-specific effects to those we observed were seen with inhibition of the anaphase promoting complex and EEL-1 ubiquitin ligases, the F-box protein MEC-15 FBXW9, as well as the cell adhesion molecule CASY-1, in prior studies at this synapse. 48,80,81,83 These collective results demonstrate GABAergic neuron-specific regulation is possible, and even common, and that the aldicarb paralysis assay may be particularly sensitive to defects in inhibitory neurons. 50 We found that GABAergic neuron-specific overexpression not only of wild type UBC-9 but also the C93S mutant increased muscle excitation (Figure 6a), suggesting UBC-9's effects may be independent of its catalytic activity; however, because of the overexpression context, we believe this does not necessarily reflect a SUMOylation-independent role for endogenous UBC-9 at this synapse.…”
Section: Tight Regulation Of Ubc-9 Activity Is Required In Gabaergic mentioning
confidence: 72%
“…In C. elegans , CASY-1A expression is not seen in cholinergic or GABAergic ventral cord motor neurons ( Thapliyal et al 2018 ). However, it is strongly expressed in several sensory neurons and interneurons located in the anterior region of the animal (Figure S1 in File S1 and see Ikeda et al 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…We have recently shown that CASY-1 is required for regulating GABA release, and, hence, maintaining normal GABAergic neurotransmission at the C. elegans NMJ ( Thapliyal et al 2018 ). In this study, we report a possible mechanism for CASY-1A-mediated regulation of excitatory cholinergic transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, rigorous analyses are warranted to address whether and how this circuit specificity is related to the altered anxiety-like behavior observed in Clstn3-cKO mice (Figure 6). A complete understanding of how Clstn3 functions will also require investigation of the potential contributions of other Clstn3 domains (e.g., LNS domain, intracellular region) to the functions of Clstn3, as was similarly shown in C. elegans (Ikeda et al, 2008;Kim and Emmons, 2017;Thapliyal et al, 2018).…”
Section: Discussionmentioning
confidence: 99%